Stylistic patterns of political communication 2.0: German and Italian Extreme Right-wing Weblogs from the Perspective of Contrastive Textology - Calpestrati, Nicolò (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
Weblogs differ in content and purpose and are today one of the most widely used forms of communication in the political arena, as they allow a direct and immediate interaction with the voters. The posted articles show stylistic features that help to shape the political ideology of the weblog. This article deals with the question of whether political weblogs reflect the prototypical features of this communicative form or whether they have individual style traits. To answer this question, a corpus of 20 articles, 10 from a German and 10 from an Italian far-right political weblog are examined from the perspective of contrastive textology. Political weblogs show a hybrid style: while on the micro level stylistic features can be traced back to a text type, the analysis of the macro level show a predominant individual style.